2023
DOI: 10.3390/metabo13111166
|View full text |Cite
|
Sign up to set email alerts
|

Tryptophan Metabolism and Gut Microbiota: A Novel Regulatory Axis Integrating the Microbiome, Immunity, and Cancer

Yingjian Hou,
Jing Li,
Shuhuan Ying

Abstract: Tryptophan metabolism and gut microbiota form an integrated regulatory axis that impacts immunity, metabolism, and cancer. This review consolidated current knowledge on the bidirectional interactions between microbial tryptophan processing and the host. We focused on how the gut microbiome controls tryptophan breakdown via the indole, kynurenine, and serotonin pathways. Dysbiosis of the gut microbiota induces disruptions in tryptophan catabolism which contribute to disorders like inflammatory conditions, neuro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(8 citation statements)
references
References 178 publications
0
8
0
Order By: Relevance
“…Previous studies have shown that the metabolism of tryptophan to serotonin acts as a regulatory axis integrating the gut microbiome, diet, immunity, and colon cancer. , Given the significant accumulation of histone serotonylation in colorectal cancer tissues, we sought to understand the functions of H3Q5 serotonylation in regulating the chromatin structures of cancer cells. In our studies, we have shown that H3Q5 serotonylation can potentiate binding to WDR5, which is a potential H3 “reader” protein and member of the MLL1 methyltransferase complex. ,, The enhanced binding affinity between H3Q5ser and WDR5 can be attributed to multiple interactions, such as the cation-π stacking between R4828 of WDR5 and the indole ring of H3Q5ser. , Although this enhanced binding had no effect on the enzymatic activity of MLL1 for H3K4 methylation, the existence of H3Q5ser could stabilize H3K4me3 from dynamic turnover by profoundly inhibiting the binding and activity of H3K4me3 erasers (such as KDM5B/C and LSD1) .…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have shown that the metabolism of tryptophan to serotonin acts as a regulatory axis integrating the gut microbiome, diet, immunity, and colon cancer. , Given the significant accumulation of histone serotonylation in colorectal cancer tissues, we sought to understand the functions of H3Q5 serotonylation in regulating the chromatin structures of cancer cells. In our studies, we have shown that H3Q5 serotonylation can potentiate binding to WDR5, which is a potential H3 “reader” protein and member of the MLL1 methyltransferase complex. ,, The enhanced binding affinity between H3Q5ser and WDR5 can be attributed to multiple interactions, such as the cation-π stacking between R4828 of WDR5 and the indole ring of H3Q5ser. , Although this enhanced binding had no effect on the enzymatic activity of MLL1 for H3K4 methylation, the existence of H3Q5ser could stabilize H3K4me3 from dynamic turnover by profoundly inhibiting the binding and activity of H3K4me3 erasers (such as KDM5B/C and LSD1) .…”
Section: Resultsmentioning
confidence: 99%
“…Third, the use of 5HTP instead of tryptophan (Trp) as a 5HT precursor allowed us to avoid the rate-limiting step in the synthesis of serotonin and to mimic the effect of increased serotonin synthesis through the chosen 5HTP dose. As opposed to Trp, which is an essential amino acid with many functions in the body (more than 90% of Trp enters the kynurenine metabolic pathway, about 5% is metabolized through the indole pathway by the gut microbiota, and only the remaining Trp is used in the serotonin synthesis [66,67]), 5HTP is only found in the serotonin synthesis pathway and is quantitatively converted to 5HT [20]. Fourth, experimenting on both male and female animals enabled us to check for the potential sex differences in the vulnerability to disbalance in 5HT homeostasis and to avoid a sex-biased interpretation of the results.…”
Section: Discussionmentioning
confidence: 99%
“…Scientific evidence shows that intestinal dysbiosis can contribute to the development of chronic constipation through modulation of the serotoninergic pathway ( 38 ).…”
Section: Discussionmentioning
confidence: 99%
“…It emerges, therefore, that there is not only a correlation between constipation and dysbiosis but also a correlation between dysbiosis and intestinal motility ( 32 ). In this respect, the combination of psyllium with Lactobacillus acidophilus and tryptophan may exert multiple effects as a regulator of gut motility and microbiota ( 31 , 32 , 38 40 ).…”
Section: Discussionmentioning
confidence: 99%